Group potency in graduate learning communities: organizational support, group size, and duration of membership - Shelton, Paul M., author; Gilley, Jerry W., advisor; Folkestad, James E., committee member; Rademacher, Robert A., committee member; Makela, Carole J., committee member; Venneberg, Donald L., committee member (Colorado State University. Libraries, 2008)
This quantitative study analyzed group potency in graduate learning communities. Group potency is the collective belief that a group can succeed, achieve, and be effective in its endeavor. The study addressed these relationships -- group potency and (a) participants’ perception of organizational support, (b) length of time participants have been together, and (c) size of the learning community, and size of the learning community and the perception of organizational support. The study used a three part questionnaire. The first section identified levels of perceived organizational support and was developed by Eisenberger. The second section measured group potency as developed from Shea and Guzzo. Finally, the third part asked for demographic data. There were 192 participants from four universities' graduate school cohorts who responded to an electronically distributed questionnaire. The findings were analyzed using Pearson's r and ANOVAs to identify relationships between the variables or differences among groups. Respondents were between the ages of 31 and 50 years (60.2%). Females accounted for 69.3% of the sample. All respondents were completing or had completed either a master’s degree or doctoral degree in business, education, human resources, or organizational development as identified by the participants, not the programs' designation. The findings suggest that there is a significant relationship between group potency and perceived organizational support. However, there were no significant relationships between length of time of membership and group potency, group size and group potency levels, and group size and levels of perceived organizational support. The implications for practice are that in graduate school cohorts, group potency can be increased by increasing students' perception that the organization supports it.
Department Head: Timothy Gray Davies.